PERAN GURU DALAM PENGEMBANGAN KURIKULUM PAI DAN IMPLEMENTASINYA DI MADRASAH DAN SEKOLAH - Aisyah Fadhilah; Suparjo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study explores the strategic role of teachers in the development and implementation of the Islamic Religious Education (PAI) curriculum in madrasahs and schools. Teachers are not only instructional executors but also curriculum developers, innovators, and evaluators who play a vital role in designing learning tools such as annual programs, semester plans, and teaching modules. Within the context of the Merdeka Curriculum, teachers are required to tailor learning to students' characteristics, Islamic values, and socio-cultural diversity. This study also highlights challenges in implementing the PAI curriculum, including limited learning facilities, low parental involvement, and unsupportive environments. Therefore, collaboration between teachers, schools, and the community is essential for the successful implementation of a holistic, adaptive, and contextual curriculum that fosters morally upright and tolerant students.